THE EFFECT OF THE CONCENTRATION SOAKING SOLUTION OF PLANTS ANT NESTS (Myrmecodia pendans) TO THE QUALITY OF CHARACTERISTICS SELAIS (Cryptopterus bicirchis) SMOKE - Razi, Muhammad Ar; Loekman, Suardi; ', Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research aimed to determite the effect of soaking solution plants ant nests on the quality of fish selais (Cryptopterus bicirchis) smoke, seen from the organoleptic, analysis of the moisture, ash, protein, fat concentration and test the antioxidant activity. The methods used in this research is an experiment that is doing an experiment making fish processing smoke and treatment soaking solution of ant nests with concentration different plants without solution ant nest S0 (0%), S5 (5%), S10 (10%) dan S15 (15%). The research showed that the treatment soaking solution of ant nests on the quality fish selais smoke with concentration 15% (S15) is most preferable treatment with characteristics of appearance is neat, fawn coloured and rather interesting (7.78), texture is compact and dry (7.16), scent is comfortable and the smell of smoke favored (6.79) and sense is tasty and the smell of smoke favored (7.00). For value of the moisture is 27.12% , ash 10.08%, protein 51.76%, and fat concentration 10.07% was and the test result of antioxidants activity is 6.09 mg/mL.Keyword : Solution plants of ant nests, soaking, selais smoked